Okkultismus im Gehäuse Institutionalisierungen der Parapsychologie im 20. Jahrhundert im internationalen Vergleich - Lux, Anna; Paletschek, Sylvia (Okkulte Moderne, 2016)
Where was the locus of parapsychology - the academic involvement with the occult - during the 20th century? In this first attempt at an international comparison, the authors examine various institutional venues, including private salons, academic societies, and universities, while also addressing prominent opponents. Essays on practical applications of parapsychology and cinematic presentations supplement their findings.